2014
DOI: 10.1021/jo501144v
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of 1,3,5-Triazine Derivatives via Controlled Cross-Cyclotrimerization of Nitriles: A Mechanism Approach

Abstract: The reaction of equimolecular amounts of a nitrile and triflic anhydride or triflic acid at low temperature produces an intermediate nitrilium salt that subsequently reacts with 2 equiv of a different nitrile at higher temperature to form 2,4-disusbstituted-6-substituted 1,3,5-triazines in moderate to good yields. This synthetic procedure has also been applied to the preparation of a 1,3,5-triazine having three different substituents. The results are explained in terms of a mechanism based on the relative stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Next, a more recent procedure for the synthesis of 2,4‐disubstituted 6‐substituted 1,3,5‐triazines by the same authors was attempted. It involved treatment of bromoacetonitrile with triflic anhydride or triflic acid in toluene at reflux . Surprisingly, in both cases the only isolated product was 2‐bromo‐4′‐methylacetophenone ( 7 ), resulting from electrophilic aromatic substitution of the solvent (Scheme B).…”
Section: Resultsmentioning
confidence: 99%
“…Next, a more recent procedure for the synthesis of 2,4‐disubstituted 6‐substituted 1,3,5‐triazines by the same authors was attempted. It involved treatment of bromoacetonitrile with triflic anhydride or triflic acid in toluene at reflux . Surprisingly, in both cases the only isolated product was 2‐bromo‐4′‐methylacetophenone ( 7 ), resulting from electrophilic aromatic substitution of the solvent (Scheme B).…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al in 2013, introduced the synthesis of pyrazolo‐1,3,5‐triazine hybrid ( P16 ) via reaction of ethoxycarbonyl thiocyanate/ethoxycarbonyl isothiocyanate with amines to form urea intermediate, which further reacted with sodium methoxide to form desired product P16 in quantitative yield (60–91 %) (Scheme 15). [22] Herrera et al in 2014, reported the novel one pot synthesis of s ‐triazine analogues P17 by controlled cross‐cyclotrimerization of nitriles in the presence of triflic anhydride at low temperatures (Scheme 16 ) [23] . This procedure was applied for the preparations of 1,3,5‐triazines having three different substituents in good yields (39–82 %).…”
Section: Synthesismentioning
confidence: 99%
“…These nitriles can be prepared from aldehydes (109) and alcohols (110) on their reaction with iodine in aqueous ammonia under microwave irradiation. The reaction time was reduced to 15–30 min, without using any base, most of the time used in classical heating methods 51 …”
Section: Green Approaches Used In Synthesis Of 135‐triazine Derivativesmentioning
confidence: 99%